The Physiological Functions of Universal Stress Proteins and Their Molecular Mechanism to Protect Plants From Environmental Stresses - Chi, Yong Hun; Koo, Sung Sun; Oh, Hun Taek; Lee, Eun Seon; Park, Joung Hun; Phan, Kieu Anh Thi; Wi, Seong Dong; Bae, Su Bin; Paeng, Seol Ki; Chae, Ho Byoung; Kang, Chang Ho; Kim, Min Gab; et al. (Frontiers in Plant Science, 2019)
Abstract Since the original discovery of a Universal Stress Protein (USP) in Escherichia coli, a number of USPs have been identified from diverse sources including archaea, bacteria, plants, and metazoans. As their name implies, these proteins participate in a broad range of cellular responses to biotic and abiotic stresses. Their physiological functions are associated with ion scavenging, hypoxia responses, cellular mobility, and regulation of cell growth and development. Consistent with their roles in resistance to multiple stresses, USPs show a wide range of structural diversity that results from the diverse range of other functional motifs fused with the USP domain. As well as providing structural diversity, these catalytic motifs are responsible for the diverse biochemical properties of USPs and enable them to act in a number of cellular signaling transducers and metabolic regulators. Despite the importance of USP function in many organisms, the molecular mechanisms by which USPs protect cells and provide stress resistance remain largely unknown. This review addresses the diverse roles of USPs in plants and how the proteins enable plants to resist against multiple stresses in ever-changing environment. Bioinformatic tools used for the collection of a set of USPs from various plant species provide more than 2,100 USPs and their functional diversity in plant physiology. Data from previous studies are used to understand how the biochemical activity of plant USPs modulates biotic and abiotic stress signaling. As USPs interact with the redox protein, thioredoxin, in Arabidopsis and reactive oxygen species (ROS) regulates the activity of USPs, the involvement of USPs in redox-mediated defense signaling is also considered. Finally, this review discusses the biotechnological application of USPs in an agricultural context by considering the development of novel stress-resistant crops through manipulating the expression of USP genes.